2018
DOI: 10.1002/elsc.201700137
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of graphene oxide‐formate dehydrogenase composites by nickel‐coordination with enhanced stability and reusability

Abstract: Featuring unique planar structure, large surface area and biocompatibility, graphene oxide (GO) has been widely taken as an ideal scaffold for the immobilization of various enzymes. In this regard, nickel‐coordinated graphene oxide composites (GO‐Ni) were prepared as novel supporters for the immobilization of formate dehydrogenase. The catalytic activity, stability and morphology were studied. Compared with GO, the enzyme loading capacity of GO‐Ni was enhanced by 5.2‐fold, besides the immobilized enzyme GO‐Ni‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…FDH activity was measured according to the methods reported . Concentration of NADH was detected at 340 nm using an Infinite 200 PRO microplate reader (TECAN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…FDH activity was measured according to the methods reported . Concentration of NADH was detected at 340 nm using an Infinite 200 PRO microplate reader (TECAN).…”
Section: Methodsmentioning
confidence: 99%
“…FDH was immobilized on the GO and GO‐PEI, respectively to investigate the activities of the enzymes before and after immobilization . FDH solution was dispersed in 1 mg/mL GO‐PEI solution mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions of individual or multienzymes have been conducted on a wide range of carriers, such as metal–organic frameworks (MOFs) [ 40 ], hydrogel [ 41 ], graphene oxide [ 42 ], liposome [ 43 ], polymersome [ 44 ], proteins [ 45 ] and DNA nanostructures [ 46 ]. These artificial scaffolds are suggested to enhance the enzyme stability, reusability or catalytic ability, expanding the applications of enzyme in different fields such as the biosynthesis of value-added chemicals.…”
Section: Construction Of the Artificial Enzymatic Reaction Systems In...mentioning
confidence: 99%
“…Lin et al 9 studied the nickel-coordinated graphene oxide composites (GO-Ni) as a novel supporter for the immobilization of formate dehydrogenase with enhanced thermal stability. Liu et al 10 demonstrated the combination of amino Fe 3 O 4 nanoparticles with GO as magnetic GO (MGO) nanocomposites for the immobilization of alcohol dehydrogenase, showing an enhanced broader range of pH stability and storage thermostability.…”
Section: Introductionmentioning
confidence: 99%